'CREATE YOUR SPACE!' LOCATING CONTEMPORARY DANCE IN OUAGADOUGOU. (5th February 2014) - Sieveking, Nadine
ABSTRACT Since the turn of the century contemporary dance has been gaining momentum as a pan-African artistic movement in which a new generation of performers is engaging. In contrast to more popular forms of 'traditional' or 'modern' performance genres, this new movement has evolved within the cosmopolitan urban elite and is driven by processes of professionalization that lead to the creation of new, border-crossing artistic spaces. These spaces are characterized by new boundaries and inequalities, related to various modes of distinction reflecting the shifting grounds of social status – gendered, generational, knowledge-based and economic. Taking an artistic 'capacity-building' project targeting female dancers in West Africa as an entry point, the article analyses how the practice of contemporary dance in Ouagadougou leads to the emergence of a translocal social space embedded in a dense network of transnational relations and connected to global art worlds. It is argued that the unequal power relations characterizing the professional art world of contemporary dance reflect the tensions and contradictions of local urban societies in the making and at the same time contribute to a reconfiguration of urban spaces where new forms of rooted cosmopolitanism can be invented.